2010
DOI: 10.1183/09031936.00035610
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of procalcitonin in community-acquired pneumonia

Abstract: The prognostic value of procalcitonin (PCT) levels to predict mortality and other adverse events in community-acquired pneumonia (CAP) remains undefined.We assessed the performance of PCT overall, stratified into four predefined procalcitonin tiers (,0.1, 0.1-0.25, .0.25-0.5, .0.5 mg?L -1 ) and stratified by Pneumonia Severity Index (PSI) and CURB-65 (confusion, urea .7 mmol?L -1 , respiratory frequency o30 breaths?min -1 , systolic blood pressure ,90 mmHg or diastolic blood pressure f60 mmHg, and age o65 yrs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 28 publications
3
115
3
8
Order By: Relevance
“…Elevation of the serum procalcitonin level in patients with CAP, unless sepsis is present, is generally minimal. 24 Schuetz et al 20 showed that although the serum procalcitonin level was significantly higher in non-survivors of CAP than in survivors, the difference between the median values was very small (0.39 ng/mL). In contrast, PCT-Q categorizes serum procalcitonin levels into only 4 grades (Ͻ 0.5, 0.5 to Ͻ 2.0, 2.0 to Ͻ 10.0, and Ն 10.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevation of the serum procalcitonin level in patients with CAP, unless sepsis is present, is generally minimal. 24 Schuetz et al 20 showed that although the serum procalcitonin level was significantly higher in non-survivors of CAP than in survivors, the difference between the median values was very small (0.39 ng/mL). In contrast, PCT-Q categorizes serum procalcitonin levels into only 4 grades (Ͻ 0.5, 0.5 to Ͻ 2.0, 2.0 to Ͻ 10.0, and Ն 10.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…ICϭ intensive care CURB-65ϭ confusion, urea nitrogen, breathing frequency, blood pressure, Ն 65 years of age A-DROPϭ age, dehydration, respiratory failure, orientation disturbance, pressure B/A ratioϭ blood urea nitrogen to serum albumin ratio half of the patients who were admitted to ICUs had serum procalcitonin levels of Ͻ 0.5 ng/mL. 20 In short, semiquantitative serum procalcitonin levels Ն 10.0 ng/mL might indicate a high probability of need for intensive care, but the lower levels of semi-quantitative serum procalcitonin cannot exclude the possibility of the need for intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…We used blood levels of C-reactive protein (CRP), PCT, white blood cell count (WBC) and pro-adrenomedullin (ProADM) from the day of admission and days 3, 5 and 7 to reflect the inflammatory response. These markers are upregulated during systemic infections and correlate with inflammation (CRP, WBC), bacterial aetiology (PCT) and disease severity/mortality and other adverse outcome risk (ProADM) [18][19][20][21][22]. For the purpose of this study, we defined 'adverse clinical course' as all-cause mortality, intensive-care unit (ICU) admission, or both, during a 30 day follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…The data from recent studies suggest that some blood markers, e.g. pro-adrenomedullin (proADM) [6][7][8][9][10][11] or procalcitonin (PCT) [12][13][14][15], mirror the severity of infection and enhance clinical risk scores for short-term prognostication. However, less extensive research has been conducted for a better understanding of factors influencing longterm mortality after initial hospitalisation of CAP patients.…”
mentioning
confidence: 99%